If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 2(-5x) = -3 Remove parenthesis around (-5x) -3x + 2 * -5x = -3 Multiply 2 * -5 -3x + -10x = -3 Combine like terms: -3x + -10x = -13x -13x = -3 Solving -13x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-13'. x = 0.2307692308 Simplifying x = 0.2307692308
| (c2/15)=88 | | -24+k=-4(6-8k) | | 2(n+5)+4= | | (c2/15)=8.8 | | 4(2.25w+3.1)-2.75=44.9 | | -18x^2-12x+12=0 | | 6(x-3)=8x+10 | | M+7=-22 | | -5(r+4)=-79 | | 6a-2=8a | | Y=5+.8x | | h(6)=-1/2x-7 | | 4x+3(2x+6)-3-x=9x+15 | | 3B+6a=-12 | | P-1.5=8 | | -3(0.25+0.25y)+2y=-3 | | 9x-32=8x-8 | | 100-4Q=M | | 10(k-3)=-2k+12 | | y^2+8=3y(y-2) | | 15w+-2w+29=5w-27 | | Tanh(x)=x | | 18-8n=4n-6(7n+2) | | 5k-19=-5-19k | | 104=4(1+8x)-7x | | 9x(x)=30 | | 2x-.5y=6 | | 132.49s+15=192.49 | | 24+21x-9x=15x+6+24 | | 5x-3+2x-6+3x-2*5x+1-4x*3-5+6=1 | | 5/8(a-2)=10 | | 6x+7=82-13 |